Literature Review: Analisa Dampak Dari Financial Ratio Dan Firm Size Terhadap Kondisi Financial Distress - Rodisna Marselin Sitompul; Sri Andini; Ratih Kusumastuti (Universitas 45 Surabaya, 2023)
Financial distress is an event of financial downturn of the company which is the beginning of the liquidation of the company. The purpose of this study is to analyze the effect of financial ratio and firm size variables on the company's financial distress. Leverage, profitability, and liquidity are the types of ratios to use. The research method used was with literature review and used 12 relevant journal articles. The conclusion of this study is that profitability variable that influence financial distress conditions while liquidity and leverage variables do not affect these conditions. Company size as the last variable also does not have a significant influence on financial distress.